Towards a Cropping System Sustainability Tool (CROSST) –Evaluating Performance of Green Manure Cover Crops in Benin and Kenya: A Pilot Study - Mukiri, Jessica; Diogo, Rodrigue V. Cao; Gbedjissokpa, Sènami G.M.; Kinyua, Michael; Hoek, Rein van der; Sommer, Rolf; Paul, Birthe K. (International Center for Tropical Agriculture, 2019)
Soil degradation poses a serious threat to food production and rural livelihoods in sub-Saharan Africa1. Nutrient mining ,as a result of unsustainable farming practices, have left the soils unfertile (Fig.1). Green Manure Cover Crops (GMCC’s) are a promising intervention to improve soil health2.Benefits from GMCC’s are well known; however, there has been low uptake. Information on how GMCC technologies impact on profits, soil health ,and ecosystem services had not been thoroughly assessed3. Therefore, a Cropping System Sustainability Tool (CROSST) was developed to better understand agro-environmental and socio-economic impacts and trade-offs of GMCC integration in cropping systems. The tool was pilot tested in Benin and Kenya under the German Federal Ministry for Economic Cooperation and Development (BMZ)/Deutsche GesellschaftfürInternationaleZusammenarbeit(GIZ) program on ‘Soil Protection and Rehabilitation for Food Security.’